Research on Patent Technology Based on Wireless Charging Patent Pools - Wu, Yuwei; Liu, Peitong; Dai, Lin; Wei, Xiaoling; Wu, Donglong (Scientific Journal of Technology, 2025)
With the in-depth transformation of the new energy vehicle industry towards "electrification and intelligence", wireless charging, as a key technology to address the inconvenience of traditional charging, has seen its patent layout and patent pool operation gradually become the core of industrial competition. This paper takes typical global wireless charging patent pools (with the EV Charging Patent Pool under Via Licensing Alliance (Via LA) as the core research object) as samples, and combines data from the AutoPat global automotive patent big data platform (as of December 2024). It systematically analyzes the current status of patent technologies in wireless charging patent pools from four dimensions: patent pool composition, core technology distribution, geographical layout characteristics, and licensing rates. This paper proposes a three-level strategy of "targeted technology R&D - standardized collaborative layout - independent patent pool construction", providing references for China’s new energy vehicle wireless charging field to break through patent barriers and enhance technological competitiveness.